Servet-i Fünûn Dönemi Edebiyatında Şiir - Özcan, Tarık (Taner NAMLI, 2022)
Servet-i Fünun dönemi Türk edebiyatı, şiirde yenileşmenin ve çözülmenin ilk somut örneklerinin görüldüğü dönemdir. Teoride Recaîzâde Mahmut Ekrem, pratikte Abdülhak Hâmid Tarhan bu edebi gelişmelerin öncüleri olmuşlardır. Ekrem, şiirlerinden daha çok poetik mahiyetteki yazılarıyla Türk şiirinin alanını genişletir ve o güne kadar Müslüman mabedi etrafında şekillenen Türk şiirinin hayatla olan irtibatını sağlar. Servet-i Fünun şiirinin kaynakları arasında en tesirli olan kişi Recaîzâde Mahmut Ekrem olmuştur. İlk döneminde eski şiirin tesirinden izler taşıyan Tevfik Fikret, yeniliğin kapısını Ekrem’in yardımlarıyla aralamıştır. Cenab’ın şiirlerindeki büyük kırılmaların kaynağı da Batı retoriğini çok iyi bilen hocası Ekrem’in tavsiyeleri olduğu kadar Fransız şiiri ve şairleridir. Bütün bunları basit bir taklitten öteye sentez düşüncesiyle açıklamanın daha doğru olacağı kanaatindeyiz.

The Servet-i Fünun period of Turkish literature is the period when the first concrete examples of renewal and dissolution in poetry were seen. Recaizade Mahmut Ekrem in theory and Abdülhak Hamid Tarhan in practice have been the pioneers of these literary developments. Ekrem expands the field of Turkish poetry with his writings that are more poetic than his poems and provides the connection of Turkish poetry, which has been shaped around the Muslim temple until that day, with life. Recaizade Mahmut Ekrem was the most influential person among the sources of Servet-i Fünun poetry. In his first period, Tevfik Fikret, who carries traces of the influence of old poetry, opened the door to innovation with the help of Ekrem. The source of the major breaks in Cenab's poems are the recommendations of his teacher Ekrem, who knows Western rhetoric very well, as well as French poetry and poets. We believe that it would be more correct to explain all this with the idea of synthesis rather than a simple imitation.
Poetry in the Literature of the Servet-i Fünun Period